ASSESSMENT METHODS OF USING RENEWABLE ENERGIES (PANGEEA, 2025)
Human economic activities, irrespective of their type, being industrial, agricultural, commercial or touristic ones, have the goal to support the increase of human beings quality of life. Beside positive direct and desired effects of diverse human economic activities these could also have sometimes negative, undesired and even unthinkable impacts on environment and society. Especially activities related to energy generation can have several inadvertent unwanted impacts on environment and society. With the goal of assuring the sustainability of our human society it is therefore implicitly required to assess not only industrial processes but also especially energy generation activities by applying economic and technological methods of approach as well as environmental and social ones. In the context of global debates related to limited availability of fossil fuels, current activities concerning electrical and thermal energy generation are focused on using renewable energy resources on a global level for assuring corresponding energy needed by the population. During the last decades, assessment methods for evaluating using odds of renewable energy resources have been applied especially in the context of the pretty new discipline called Technology Assessment. Moreover, even new integrative assessment methods have been developed for simultaneously considering interdisciplinary aspects in assessing procedures. Technology Assessment has been firstly designed in the United States and then it became well known in Western Europe as well, currently its specific assessment methods being fairly used on a worldwide level. In order to carry out environmental assessment studies of using renewable energy resources the pretty known tool of Life Cycle Assessment, LCA can be applied and successfully used. In the present article, general notions regarding assessment methods especially environmental ones will be considered. As an example a Fuzzy-Logic based integrative assessment method will be presented, where possibilities for assessing the regional use of renewable energy resources will be debated, after presenting the working way of Fuzzy Logic.
Keywords: renewable energy resources; assessment methods; environmental impact assessment; Fuzzy Logic; energy generation; life cycle assessment